Bibliometric Mapping of Research on Tax Justice and Equity in Global Financial Systems - Judijanto, Loso (West Science Accounting and Finance, 2025)
This study does an extensive bibliometric analysis of worldwide research on tax justice and equity in financial systems, utilizing data from Scopus (2010–2025) and analytical tools like VOSviewer and Bibliometrix (R-package).  The analysis delineates main themes, prominent authors, collaborative networks, and temporal research trends that influence the tax justice discourse.  The findings indicate three predominant thematic clusters: fiscal stability and global governance; sustainability and environmental taxes; and social equity within fiscal systems.  The United States, China, and Germany are prominent contributors, while the rising involvement of developing economies indicates a steady variety of viewpoints.  The collaboration networks among scholars such as Janský, Meinzer, and Cobham demonstrate a strong interaction between empirical research and the promotion of transparency.  The report emphasizes ongoing disparities in regional representation and language inclusivity while highlighting an increase in interdisciplinarity across economics, law, and governance.  This paper delineates the intellectual framework and research boundaries of tax justice, offering policymakers and scholars a strategic basis for advancing fair, sustainable, and transparent fiscal reforms worldwide.